PENERAPAN METODE ABDULLAH NASIH ULWAN DALAM MENGATASI BULLYING PADA SISWA DI MTS ASSYIFA JATIAGUNG LAMPUNG SELATAN: SEBUAH PENDEKATAN PENDIDIKAN KARAKTER BERBASIS NILAI ISLAM - Aini, Rizkya Fathiatul; Syafe’i, Imam; Septuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the application of Abdullah Nasih Ulwan's method in addressing bullying at MTs Assyifa Jatiagung Lampung Selatan. The applied method includes five main principles: role modeling, good habits, attention, advice, and educational punishment. Through this approach, it is expected to foster empathetic, respectful students and reduce bullying behavior among peers. The results of the study show that the implementation of Ulwan's method is effective in reducing bullying, both verbal and physical. Students previously involved in bullying began to exhibit positive changes in behavior and social interactions. Teachers also reported improvements in the learning environment, which became more conducive to positive interactions. This research confirms that character education based on Islamic values, as applied in Ulwan's method, can be an effective solution to the bullying problem in schools.